Psychometric properties of a social and emotional competence assessment for middle school students - Clark McKown; Nicole Russo-Ponsaran; Matthew Wronski; Ashley Karls (Social and Emotional Learning: Research, Practice, and Policy)
This study describes the rationale, design, development, and technical properties of SELweb MS, a direct assessment of social and emotional competencies in middle school students. Assessment and item design were iteratively developed with input from youth and experts to measure five domains: Self-Awareness, Self-Management, Social Awareness, Relationship Skills, and Responsible Decision-Making. Across three studies involving more than 3600 students, SELweb MS subtest scores demonstrated moderate to strong internal consistency and six-month temporal stability reliability. In addition, confirmatory factor analysis supported a five-factor structure corresponding to the five competencies the assessment was designed to measure. Associations with alternative measures of the same competencies supported convergent validity and provided mixed support for discriminant validity. Finally, performance on SELweb MS was positively associated with teacher-rated social skills and academic engagement and negatively associated with problem behaviors. Impact Statement: This paper described SELweb MS, a novel middle school assessment of social and emotional competencies. The paper includes three studies that together describe the iterative development of SELweb MS and its psychometric properties, including score reliability, structural validity, and criterion-related validity. Results suggest that scores derived from SELweb MS have good reliability and evidence of validity for characterizing student social and emotional strengths and needs.